Kediri Royal and Agrarian Batik Motifs as Local Wisdom Based Innovation for Creative Industry Products - Talisa Fasya Laksita Putri; Deny Arifiana; Indarti Indarti (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2026)
The creative batik industry faces the challenge of declining interest among the younger generation due to the perception of batik as a traditional product that is less relevant to contemporary lifestyles. This condition calls for the development of innovative and contextual batik without losing its local wisdom values. Kediri, with its historical background of the Kediri Kingdom and strong agrarian culture, has visual and symbolic potential that can be developed as a source of innovation for contemporary batik motifs. This study aims to describe the process of developing batik motif designs with themes of the Kediri kingdom and agriculture, as well as to create batik prototypes as creative industry products for dissemination through exhibitions. The method used is design-based research with a Double Diamond Model based on a descriptive qualitative approach. The novelty of this study lies in the integration of royal agrarian cultural narratives of Kediri within a structured Double Diamond design framework for contemporary batik development. The results of the study produced five contemporary batik motifs that were developed into master designs measuring 100 × 50 cm, then developed into 200 × 100 cm and realized in the form of batik prototypes. One of the leading designs, namely the Garuda Sri Wibawa theme, received positive responses from target consumers aged 20–45 years, particularly in terms of visual preference, perceived cultural relevance, and product appeal, and was displayed in an exhibition at the Surabaya State University art gallery as a form of dissemination of the work. These findings indicate that Kediri's royal and agrarian themed batik motifs possess visual, cultural, and appreciative values relevant to the development of contemporary batik creative industry products.